Importance of inspection and investigations in bank management - Suntharalingam, R. (University of Jaffna, 2016)
Banking is based on Confidence. Banks must adopt measures to enhance the public confidence on the one hand and minimize faults and misdemeanors. Continuous monitoring of the activities of the Bank becomes imperative with the set goal of maintaining high standards of performance by its cadre and the services available and rendered and to minimize all ill effects arising out of the actions of the cadre and services offered. Inspection is monitoring to assess the performance on a recurring basis to ensure compliance with set standards and norms - more a guiding process than a fault finding process. Investigations can arise out of the above routine inspections, complaints, reports from various sources; follow up on inspection reports etc. Both have to be fine-tuned to maintain the tripartite relationship in the Bank on an even keel - the clientele, the cadre and the Management. The Banks have separate departments with their own cadres functioning exclusively in that capacity. The decentralized units' supplement it. Controversy is there as to its effectiveness in the light innovations in functional distribution Irrespective of the form or the composition, functions have to be meticulously carried out if the Bank is to continue as an orderly unit ,especially facing competitive banking. The staff selected for these functions must be more of a guide, philosopher and friend than a one wielding the big stick. There is a certain amount of coercive authority which a manager may lack because of familiarity and this is useful in bringing about the desired orderliness and tranquility. Unlike those serving the clientele these functions do not yield immediate profits but their effectiveness is felt when there is orderliness and even tranquility. Absence can lead to open defiance from within and out. It has a salutary effect on the staff that may meander in the absence of this strong hand.
Keywords: Banks; Clientele; Cadre management; Inspections; Investigations